Impact of insomnia on self-perceived health in the elderly - Silva, Janiciene; Truzzi, Annibal; Schaustz, Fayanne; Barros, Roberta; Santos, Marisa; Laks, Jerson (Arquivos de Neuro-Psiquiatria, 2017)
Health self-perception is a strong indicator of the health of a population. To investigate the association between self-perceived health, and sociodemographic and clinical factors in a sample of elderly outpatients in Rio de Janeiro.A sample of 345 elderly patients was assessed with an anamnesis, Lawton and Brody’s Scale, Katz Index, Geriatric Depression Scale, Timed Up and Go Test, and Study of Osteoporotic Fracture Index. Logistic regression analyses were performed to investigate the predictors of self-perceived health.Risk of falls, frailty, functional performance on the Instrumental Activities of Daily Living, insomnia, and familial support were related to self-perceived health. Insomnia was the variable that strongly influenced self-perceived health (OR = 0.47, CI 95%: 0.28–0.80, p = 0.01) in our sample.The investigation of insomnia in the elderly should be routinely performed in primary care, because of the negative impact it imposes on the health of this population.
Keywords: self concept; aged; sleep initiation and maintenance disorders